The Value of Concept: Lessons from the Evolution of Antibiotic Resistance. (May 2016) - Antonovics, Janis
Abstract: The evolution of resistance to antibiotics in disease causing pathogens is a major world‐wide threat to human health. This paper explores why regulatory, funding and institutional structures have inadequately addressed this issue, focusing on data from the US, but emphasizing that these issues are of global scope and applicability. There is an increasing call for serious acceptance of evolutionary biology by the medical community, but the failure to apply evolutionary ideas to the problem of antibiotic resistance continues. These ideas are deceptively simple in their basic formulation, but require sophisticated expertise when it comes to applying them in practice and to human health. The divergent histories of evolutionary biology and medical research have self‐referential constituencies in each field. The field of evolutionary biology does not see the applied issues associated with antibiotic resistance as part of its remit. At the biomedical research level, funding for research on evolution of antibiotic resistance is paltry compared to its importance as a health threat, regulatory requirements do not address evolutionary issues, institutional structures dealing with the issue are undeveloped, and there is even avoidance of the word 'evolution' in the context of antibiotic resistance. Current approaches to antibiotic resistance invoke evolutionary principles at a such a naive level that what is put forward are ineffective seat‐of‐the‐pants rules that have no strong theoretical basis and are almost always in desperate need of justification through evidence‐based research. Clear solutions exist but their implementation remains problematic. Abstract : There is a potential catastrophe when the most important factor limiting our efforts to control infectious disease and antibiotic resistance, namely evolution, takes a minor stage in the biomedical research and regulatory community.